Incidence of cesarean delivery among users of a private health plan - Barbosa, Jaqueline F.; Toé, Thatiana F. Dal; Simões, Priscyla W. (Medicina (Ribeirao Preto), 2015)
Study model: Study of Incidence. Objective: To know incidence of cesarean at a private health plan, analyze the main indications of this, the APGAR scores of neonates, and to describe the characteristics of women who undergo this procedure, analyzing age, occupation and marital status. Methods: an ecological, descriptive and temporal study was realized with data obtained in a private health plan of Criciúma in the period from January to December of 2010. Results: We analyzed medical records of 30 women all mothers attending a private health plan during the year 2010. The incidence of cesarean section was 80%, and 20% of normal birth. The main indications were cephalopelvic disproportion (50%) and prior cesarean (16.7%). Women undergoing cesarean section had an average age of 30.54 years (± 5.42), 66.7% work and 87.5% had a stable relationship. The average APGAR of the newborns was 8.96 (± 0.20) at 1 minute and 9.08 (± 0.28) at 5 minutes. We found a significant association between the mode of delivery and the expenses, with the cesarean greater than vaginal deliveries (p = 0.013). Conclusions: The incidence of cesarean in private health plans studied was high, the major indication was the Cephalopelvic Disproportion, with the cesarean greater than vaginal deliveries. Therefore, we suggest future studies on the subject, so that it best characterized the incidence of cesarean, whereas this question varies according to the model of health in each country and sociocultural characteristics.